The relationship between fear of death and nurses' moral performance in the COVID-19 pandemic - Sahel Darderafshi; Arezou Karampourian; Salman Khazaei; Mahnaz Khatiban (Acta Psychologica)
Introduction: One of the first groups involved in the COVID-19 pandemic were nurses who faced the fear of death. This study was conducted with the aim of determining the relationship between fear of death and nurses' moral performance in the COVID-19 pandemic in 2022. Method: In this cross-sectional study, 275 nurses participated in the study. The combination of stratified and convenience sampling was used for choosing participants. The data were collected using a checklist of demographic information, the Robert Templer Death Anxiety Scale, and the Asahara Moral Performance Questionnaires. Data were analyzed using t-test, Pearson correlation and linear regression analysis using SPSS 22 software. Findings: The study involved 275 nurses, revealing a mean age of 30.96 years, with a majority being female (63.27 %) and married (57.82 %). A significant proportion (73.45 %) had been affected by COVID-19. The findings indicated that fear of death scores were influenced by familial infection history, with nurses whose fathers had not been infected reporting higher scores (β = 0.93, P < 0.001). In contrast, nurses whose spouses had been infected showed lower fear scores (β = −0.48, P < 0.05). The work environment impacted fear levels, with nurses in emergency and intensive care units experiencing significantly lower fear than those in oncology (β = −2.63 and β = −2.5, respectively, P < 0.05). Moreover, moral performance scores increased with age (β = 0.36, P < 0.05) and were higher in nurses without a history of COVID-19 (β = 11.77, P < 0.05). Conversely, moral performance decreased with overtime hours worked (β = −0.1, P < 0.05). Notably, fear of death did not significantly correlate with moral performance during the pandemic (β = 0.08, P = 0.74). Conclusion: In this study, despite facing the challenge of fear of death, nurses have tried to adhere to ethical principles, however, it is recommended to investigate other factors affecting the moral performance of nurses.